(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
The fossil record of sciaenid fishes (based on both otoliths and osteological finds) from the Neogene of the Paratethys is reviewed. The species Labrax (=Morone) multipinnatus Gorjanović-Kramberger, 1882 from the Sarmatian of Croatia (Sv. Nedelja) that was originally described as a sea bass of the family Moronidae is re-assigned to the extant croaker genus Argyrosomus. Two new genera and species of sciaenid fishes are described based on a single skeleton each, namely Landinisciaena popovi gen. et sp. nov. from the Tarkhanian (Lower/Middle Miocene) North Shirvanskaya Formation exposed along the Pshekha River, North Caucasus, Russia, and Croatosciaena krambergeri gen. et sp. nov. from the Sarmatian s.s. (Middle Miocene) deposits of Dolje in the nearby of the city of Zagreb, Croatia. The holotype of the former taxon possesses a well-preserved saccular otolith in situ (first record of in situ croacker otolith in Europe) similar to the otoliths of the extant genus Atractoscion. The otolith-based Ottnangian species Atractoscion elongatissimus Schwarzhans, 1993 is transferred to the genus Landinisciaena gen. nov. A comprehensive revision of the Neogene otholith-based sciaenid record from Paratethys resulted in the recognition of three new genera (Chaoia gen. nov., Pontosciaena gen. nov. and Leptosciaena gen. nov.) as well as in the description of a new species L. caputoi sp. nov. from the uppermost Messinian (Lago-mare phase) of Italy. A number of known otholith-based species were either synonymized or assigned to a new generic affiliation. The complex biogeographic history of the Neogene Paratethyan sciaenids (based on both otoliths and skeletal records) is discussed, resulting in the recognition of a vanished “sciaenid bioprovince”.